The factors influence job satisfaction among childcare employees: A study in Kedah - Nur Zalikha 'Akalili', Muhamad Kashfi (2018)
This study aims to look at the factors that influence job satisfaction among childcare employees in the Kedah State. The main objective of this research was to identify any correlation between salary, internal communication, rewards, working hour, and job satisfaction. This study was conducted using quantitative methods where data were collected using a set of questionnaires. Questionnaires’ books were used to obtain feedback from the respondents. The study sample consisted of employees of childcare center in the Kedah State which has a total of 234 respondents participated in this study. The findings showed that there is a positive relationship between salary, internal communication, rewards and working hour and job satisfaction. This indicates that satisfied employees working in their respective organizations. This study has provided a better understanding of the factors that influence job satisfaction in the childcare centre. Results of this study provide benefits to the centre, particularly the management in knowing and measuring the level of satisfaction of their employees.